2023
DOI: 10.1101/2023.04.24.538076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adipocyte PI3K Links Adipostasis with Basal Insulin Secretion Through an Adipoincretin Effect

Abstract: Inhibitors of insulin-PI3K signaling potently induce insulin secretion in-vivo, demonstrating that insulin secretion is governed by feedback control. Resolving the mechanism of this feedback is necessary to understand hyperinsulinemia and insulin resistance and to develop optimal PI3K-targeted therapies. Adipose tissue-specific knockout mice for the insulin receptor, or AKT1 and AKT2, are severely lipodystrophic. Thereby, the role of adipocyte insulin signaling in the feedback control of insulin secretion rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…As described in Figure 2 , under normal physiological conditions, insulin binds to the insulin receptor located on the cellular membrane of insulin-sensitive tissues, primarily including muscle, AT, and the liver [ 16 , 79 ]. This interaction gives rise to a series of events that involve insulin receptor substrate signaling, ultimately leading to an increase in cellular glucose uptake and the activation of the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway [ 80 ]. This process can increase the expression of the gene that is responsible for encoding the glucose transporter-4 (Glut4), promoting the translocation and integration of these components into the cell membrane, thereby facilitating the transportation of sugar into the cells ( Figure 2 ).…”
Section: The Mechanism Of Insulin Resistance In Peripartum Dairy Cowsmentioning
confidence: 99%
“…As described in Figure 2 , under normal physiological conditions, insulin binds to the insulin receptor located on the cellular membrane of insulin-sensitive tissues, primarily including muscle, AT, and the liver [ 16 , 79 ]. This interaction gives rise to a series of events that involve insulin receptor substrate signaling, ultimately leading to an increase in cellular glucose uptake and the activation of the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway [ 80 ]. This process can increase the expression of the gene that is responsible for encoding the glucose transporter-4 (Glut4), promoting the translocation and integration of these components into the cell membrane, thereby facilitating the transportation of sugar into the cells ( Figure 2 ).…”
Section: The Mechanism Of Insulin Resistance In Peripartum Dairy Cowsmentioning
confidence: 99%
“…Insulin also functions as an adipostatic signal in the brain and reaches the brain via saturable transport. Glucose stimulates insulin production in the pancreas through body fat levels [ 110 ]. Thus, when obesity is present and insulin resistance is established, the pancreas secretes more insulin and excess insulin results in increased fat storage in the adipocytes [ 111 ].…”
Section: Neuroendocrine Interactions In Energy Metabolismmentioning
confidence: 99%
“…In fact, stimulation of β3-adrenergic receptor in the AT induces insulin secretion while reducing blood glucose levels ( Grujic et al 1997 ). Similarly, a preprint recently demonstrated that acute AT-specific inhibition of PI3K activity leads to an increased insulin secretion without increasing glycaemia ( Becattini et al 2023 ). Both models are associated with increased FFA levels.…”
Section: Introductionmentioning
confidence: 99%